(untitled) (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: Hydrogen peroxide (H2O2) was used for the activation of lactoperoxidase system on preservation of milk. Materials and methods: Milk samples were collected from Bangladesh Agricultural University dairy farm. The collected milk samples were added with 0.02, 0.04, 0.06, 0.08, 0.10, 0.12 and 0.14% of 10% H2O2 along with control one. All milk samples were kept at room temperature (28-310C). Flavor, clot on boiling (COB), acidity %, and methylene blue reduction (MBR) test were observed every one hour interval. Results: The milk samples were acceptable in terms of flavor up to 18 h at 0.14% H2O2. Similarly, this milk sample took maximum time (19 h) to give COB positive test. Acidity % was within normal range for 0.02, 0.04, 0.06, 0.08, 0.10, 0.12 and 0.14% H2O2 treated milk samples up to 8, 9, 11, 12, 12, 14, 17 and 18 h, respectively. Significant difference (P<0.01) was found among the levels of H2O2 in acidity development at every observation hour except 0 hour. In MBR test, control sample was decolorized at 7 h and H2O2 treated milk samples were decolorized after 8 to 13 h depending on the level of added H2O2. Conclusion: Based on the results, it may be recommended that 0.14% H2O2 is suitable to extend the milk shelf-life where milk cooling facilities are not available. http://doi.org/10.5455/javar.2017.d236